2019
DOI: 10.1371/journal.pone.0217029
|View full text |Cite|
|
Sign up to set email alerts
|

Energy expenditure differences across lying, sitting, and standing positions in young healthy adults

Abstract: The time spent in sedentary behaviour represents an important public health burden. To reduce sedentary time in the general population, the simplest, most effective, and most accessible method is to decrease lying and sitting time. We aimed to compare differences on energy expenditure (EE) across lying, sitting, and standing positions; and to analyse the associations between the change on EE of changing from one position to another and anthropometric and body composition parameters in young healthy adults. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Sit-stand desks have been a commercial success owing to the expectation that standing significantly increases energy expenditure reflected by changes in oxygen consumption due to contraction of leg muscles to maintain such posture. In our review of 15 studies of sit-stand desks comprising almost 500 subjects, approximately equally divided among men and women, mean age 30 years, range 22 to 48 years, mean standing oxygen consumption was only 9% greater than sitting with a range from 4 to 12% [30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. GJ increased seated oxygen consumption by about 15% with no significant difference between men and women.…”
Section: Energy Expenditurementioning
confidence: 99%
“…Sit-stand desks have been a commercial success owing to the expectation that standing significantly increases energy expenditure reflected by changes in oxygen consumption due to contraction of leg muscles to maintain such posture. In our review of 15 studies of sit-stand desks comprising almost 500 subjects, approximately equally divided among men and women, mean age 30 years, range 22 to 48 years, mean standing oxygen consumption was only 9% greater than sitting with a range from 4 to 12% [30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. GJ increased seated oxygen consumption by about 15% with no significant difference between men and women.…”
Section: Energy Expenditurementioning
confidence: 99%
“…REE is usually measured with the subject in the supine position or calculated by estimate equations based on the physical characteristics of trial subjects [12]. Some studies reported no EE differences between lying and sitting when the subject's posture was held strictly [13][14][15][16][17]. However, it is hard to hold the posture exactly, and movements occur in a natural position.…”
Section: Introductionmentioning
confidence: 99%
“…Then, given the pre-activation of pre-synaptic circuitry in standing position, it can be hypothesized that spinal excitability can be increased to a greater extent when practicing MI in standing posture. Regarding ANS and cardiometabolic modulations from sitting to standing, while increased sympathetic and decreased parasympathetic activity associated with greater cardiorespiratory response are often observed, EE and, overall, metabolic adjustments are not consistently reported ( Miles-Chan et al, 2013 ; Miles-Chan and Dulloo, 2017 ; Amaro-Gahete et al, 2019 ). However, it has been shown that the metabolic changes associated with the standing posture vary widely between individuals, indicating that this position is highly sensitive to slight mild perturbations, in contrast to the more stable seated position.…”
Section: Introductionmentioning
confidence: 99%